2D Intrinsic Ferromagnets from van der Waals Antiferromagnets - Miao, Naihua; Xu, Bin; Zhu, Linggang; Zhou, Jian; Sun, Zhimei (Journal of the American Chemical Society, 2018)
Intrinsically ferromagnetic 2D semiconductors are essential and highly sought for nanoscale spintronics, but they can only be obtained from ferromagnetic bulk crystals, while the possibility to create 2D intrinsic ferromagnets from bulk antiferromagnets remains unknown. Herein on the basis of ab initio calculations, we demonstrate this feasibility with the discovery of intrinsic ferromagnetism in an emerging class of single-layer 2D semiconductors CrOX (CrOCl and CrOBr monolayers), which show robust ferromagnetic ordering, large spin polarization, and high Curie temperature. These 2D crystals promise great dynamical and thermal stabilities as well as easy experimental fabrication from their bulk antiferromagnets. The Curie temperature of 2D CrOCl is 160 K, which exceeds the record (155 K) of the most-studied dilute magnetic GaMnAs materials, and could be further enhanced by appropriate strains. Our study offers an alternative promising way to create 2D intrinsic ferromagnets from their antiferromagnetic bulk counterparts and also renders 2D CrOX monolayers great platform for future spintronics.